2015
DOI: 10.1016/j.ymssp.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of beamforming for detecting an acoustic source inside a cylindrical shell filled with a heavy fluid

Abstract: The acoustic detection of defects or leaks inside a cylindrical shell containing a fluid is of prime importance in the industry, particularly in the nuclear field. This paper examines the beamforming technique which is used to detect and locate the presence of an acoustic monopole inside a cylindrical elastic shell by measuring the external shell vibrations. In order to study the effect of fluid-structure interactions and the distance of the source from the array of sensors, a vibro-acoustic model of the fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…From the detection on a threshold criterion at the output of beamforming (instead of the reference sensor), this gain allows the improvement of the detection rate while limiting the array sensibility to false alarms. The works of Moriot et al (2015) showed promising results in term of array gain, both numerically and experimentally. However, the numerical results were obtained by using simple academic models (infinite plate in Moriot et al (2012) or infinite cylindrical shell in Moriot et al (2015)) supposing uncorrelated background noise.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…From the detection on a threshold criterion at the output of beamforming (instead of the reference sensor), this gain allows the improvement of the detection rate while limiting the array sensibility to false alarms. The works of Moriot et al (2015) showed promising results in term of array gain, both numerically and experimentally. However, the numerical results were obtained by using simple academic models (infinite plate in Moriot et al (2012) or infinite cylindrical shell in Moriot et al (2015)) supposing uncorrelated background noise.…”
Section: Introductionmentioning
confidence: 97%
“…Beamforming over an array of sensors is of main interest due to its ability to increase the signal-to-noise ratio of the acoustic signal induced by the water-sodium reaction, generally masked by the SGU background noise as shown by Kim et al (2010). Moriot et al (2015) had considered the conventional beamforming (called sometimes the Bartlett beamforming) based on a knowledge of the source to be detect and by supposing that the background noise is spatially uncorrelated. In the numerical applications, the source was supposed to be an acoustic monopole (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural Health Monitoring (SHM) techniques can reduce maintenance costs significantly by switching from the schedule-based maintenance to a condition-based maintenance, and by allowing the use of lighter materials such as composite or sandwich panel in the case of aerospace structures [1]. SHM has been studied for decades, leading to the development of a large panel of techniques [2,3,4,5,6,7,8,9,10,11,12,13,14,15]. Among them, techniques based on guided wave (GW) propagation with piezoceramic transducers are cost-effective and allow a quick on-demand inspection of large areas over thin metallic and composite structures [16].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, vibration based beamforming has been studied to localize acoustic sources inside a cylindrical shell filled with heavy fluid. 9 The first contribution of the present work is the use of the FAT, usually implemented for the localization of structure borne sources, for the identification of an acoustic pressure field exciting a wall. Recent efforts in that domain might however be cited, concerning the identification of a diffuse field 10 or a turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%